Pathogenicities of rice blast (Pyricularia oryzae Cavara) isolates from Kenya - Fukuta, Yoshimichi; Telebanco-Yanoria, Mary Jeanie; Hayashi, Nagao; Yanagihara, Seiji; Machungo, Catherine Wanjiku; Makihara, Daigo (Scientific Societies, 2019)
A total of 99 isolates of rice blast (Pyricularia oryzae Cavara) were collected from 2010 to 2015 from four regions in Kenya: Kirinyaga County and Embu County, Kisumu County, Tana River County, and Mombasa County. The pathogenicities of these isolates were clarified based on the reaction patterns of Lijiangxintuanheigu and differential varieties (DVs) targeting 23 resistance genes. The frequency of virulent isolates was high for DVs for Pib, Pia, Pii, Pi3, Pi5(t), Pik-s, Pik-m, Pi1, Pik-h, Pik, Pik-p, Pi7(t), Pi19(t), and Pi20(t); low for DVs for Pish, Pi9(t), Piz-5, and Piz-t; and intermediate for the remaining DVs for Pit, Piz, Pita-2, Pita, and Pi12(t). These blast isolates were classified into three cluster groups: Ia, Ib, and II. The frequencies of virulent isolates to DVs for Pit, Pii, Pik-m, Pi1, Pik-h, Pik, Pik-p, Pi7(t), Piz, and Pi12(t) differed markedly between clusters I and II, and those of DVs for Pib, Pit, Pia, Pi3, Pita-2, Pita, and Pi20(t) differed between Ia and Ib. The frequencies of cluster groups in the four geographical regions were different. A total of 62 races were found, with 19 blast isolates categorized into one race (U63-i7-k177-z00-ta003), whereas the other races included only some isolates in each.